The girl who played with fire - Larsson, Stieg, 1954-2004; Keeland, Reg, 1943- (New York : Vintage Books, 2009)
On the eve of publisher Mikael Blomkvist's story about sex trafficking between Eastern Europe and Sweden, two investigating reporters are murdered. And even more shocking for Mikael Blomkvist: the fingerprints found on the murder weapon belong to Lisbeth Salander--the troubled, wise-beyond-her-years genius hacker who came to his aid years before
Contains an excerpt from: The girl who kicked the hornet's nest
Sequel to the Girl with the dragon tattoo
Originally published in Swedish : Stockholm : Norstedts, 2006
Translation originally published: Great Britain : MacLehose Press, 2009
Sumbangan oleh Nona Kartina Francis/Umum/Praklinikal
Keywords: Human trafficking -- Fiction; Journalists -- Sweden -- Stockholm -- Fiction; Computer hackers -- Sweden -- Stockholm -- Fiction; Murder -- Investigation -- Fiction; Stockholm (Sweden) -- Fiction